Management Roles & Leadership Skills to Attract Venture Capital in Switzerland - Kendzia, Michael J.; Eugster, Robin (Archives of Business Research, 2022)
Startups constitute an essential component of a working market economy and foster economic growth, employment as well as technological progress. However, managing and leading companies at an early growth stage poses an enormous challenge, as investment failure amounts to approximately 75%. That said, receiving venture capital is all but an easy task and only 1% of investment opportunities considered qualify for an investment. Against this backdrop, the aim of this article is to identify particular management and leadership skills that attract venture capital more successfully than others do. The investigation finds that management-related criteria appear to be the most important factor for Swiss venture capitalists. Especially the track record of founders and the diversity of backgrounds within the startup’s core team were considered relevant.